Multiple Neural Correlates of Detection in the Human Brain - Shulman, Gordon L.; Ollinger, John M.; Linenweber, Martin; Petersen, Steven E.; Corbetta, Maurizio (Proceedings of the National Academy of Sciences - PNAS, 2001)
We used event-related functional MRI to examine the neural consequences of detecting the presence or absence of a stimulus. Subjects detected a brief interval of coherent motion embedded in dynamic noise that was presented throughout a test period. Several brain regions, including V1/V2, middle temporal complex (MT+), left intraparietal cortex, and the frontal eye field, were activated at the onset of the dynamic noise, irrespective of whether a coherent motion target was presented early or late in the test period, or not at all. These regions, many of which were motion sensitive, were likely involved in searching for and detecting the target. The blood oxygenation level-dependent signal in these regions was higher in trials in which a target was detected than in trials in which it was missed or not presented, indicating that these regions were modulated by detection. Moreover, the blood oxygenation leveldependent signal in these regions decayed quickly once a target was detected, even though the dynamic noise continued to be displayed, indicating that they were shut down after detection. Therefore, detection-related modulations occurred in the same regions that accumulate target information over time, in agreement with current psychological and neural models of detection. Many other regions, however, including areas in prefrontal cortex and anterior cingulate, were not involved in searching for a target. In these regions, activation began early in the test period when an early target was detected but began late in the test period when a late target was detected or when a response was correctly withheld in the absence of a motion target. The signal in these regions was therefore triggered by a discrete event during the test interval that was related to presence-absence detection.